Sistem Pelaporan Jalan Rusak Berbasis Web Dengan Peta Interaktif Menggunakan Metode Extreme Programming - Rizki Saputra; Ridwan Setiawan (Jurnal Algoritma, 2026)
Garut Regency faces problems with road damage, which affects community mobility and increases the risk of accidents. The reporting process has so far been conducted manually or via social media, making it difficult to track, poorly documented, and slow to follow up. This study aims to design and develop a web-based damaged road reporting system that can be accessed by the public and managed by the Public Works and Spatial Planning Office (Dinas PUPR) of Garut Regency. The method employed is Extreme Programming (XP) with the stages of Planning, Design, Coding, and Testing. The developed system provides features such as registration, login, report creation with photos, descriptions, damage levels, and automatic GPS-based location. Each report is verified by sub-district officers before being forwarded to the Dinas PUPR. The system also includes an interactive map powered by Leaflet.js, a commenting feature, and a WhatsApp icon for direct communication with reporters. System testing was conducted using Blackbox Testing with a State Transition Testing approach and the System Usability Scale (SUS) for user acceptance testing. The results show that all functions operate as designed, with an average SUS score of 85.8 (Grade A+, Best Imaginable). This study concludes that the developed web-based damaged road reporting system can improve the efficiency and transparency of the reporting process, accelerate follow-ups, and increase public participation. For the government, the system provides more accurate and well-documented report data, which can serve as a reference for prioritizing road repairs in Garut Regency.